The clinical utility and safety of biomarker-guided immunosuppression withdrawal in liver transplantation: the LIFT prospective RCT - Julien Vionnet; Rosa Miquel; Juan G Abraldes; Juan-Jose Lozano; Pablo Ruiz; Miquel Navasa; Aileen Marshall; Frederik Nevens; William Gelson; Joanna Leithead; Steven Masson; Elmar Jaeckel; et al. (Efficacy and Mechanism Evaluation)
Background Long-term surviving liver transplant recipients can spontaneously develop operational tolerance, which allows them to completely discontinue their immunosuppression, but we lack validated tools to predict the likelihood of rejection following immunosuppression withdrawal. A previous clinical trial showed that a logistic regression algorithm including the transcript levels of a set of five genes in a liver biopsy could predict the success of immunosuppression withdrawal with high sensitivity and specificity. Objective To determine if the use of a liver tissue transcriptional test of tolerance to stratify liver recipients prior to immunosuppression withdrawal accurately identifies operationally tolerant recipients and reduces the incidence of rejection, as compared with a control group in whom immunosuppression withdrawal is performed without stratification. Design and methods Prospective, multicentric, phase IV, biomarker-strategy design trial with a randomised control group in which adult liver transplant recipients were randomised 1 : 1 to either: (1) non-biomarker-based immunosuppression weaning (Arm A); or (2) biomarker-based immunosuppression weaning (Arm B). Setting and participants Adult liver transplant recipients ≥ 3 years post transplant (≥ 6 years if age ≤ 50 years old) with no history of autoimmunity or recent episodes of rejection, normal allograft function, and no significant histological abnormalities in a baseline screening liver biopsy, recruited from 12 transplant units in United Kingdom, Germany, Belgium and Spain. Intervention Enrolled patients underwent a screening liver biopsy to exclude the presence of subclinical allograft damage. Eligible participants randomised to Arm A underwent gradual discontinuation of immunosuppression. Among participants allocated to Arm B, only those found to be biomarker-positive were offered immunosuppression withdrawal, while biomarker-negative participants remained on their baseline immunosuppression. Patients who completely discontinued immunosuppression and maintained stable allograft function underwent protocol liver biopsies at 12 and 24 months after immunosuppression withdrawal. Main outcome measure Development of operational tolerance, defined as the successful discontinuation of immunosuppression with maintenance of normal allograft status 12 and 24 months after immunosuppression withdrawal. Results One hundred and twenty-two patients were eligible to participate in the trial, 116 were randomised (58 to Arm A and 58 to Arm B), 80 initiated immunosuppression withdrawal and 34 were maintaining on their baseline immunosuppression. Among the 80 patients who initiated withdrawal, 54 (67.5%) developed clinically apparent rejection, 22 (27.5%) successfully discontinued immunosuppression, 21 underwent a liver biopsy and 13 (16.3%) met the histological criteria of operational tolerance at 12 months after immunosuppression discontinuation. The transcriptional tolerance biomarker was not accurate at identifying patients meeting the operational tolerance criteria [odds ratio 1.466, 95% confidence interval (CI) 0.326 to 9.215; p = 0.744; Sensitivity (Sn) 54%, Specificity (Sp) 42%, positive predictive value 16%, and negative predictive value 81%, with an accuracy of 44%]. Due to the poor diagnostic performance of the test, the trial was terminated prematurely following an interim analysis of the results. No patients lost their grafts as a result of rejection during the study duration. Conclusions In selected liver transplant recipients, immunosuppression withdrawal proved to be feasible, but was successful in a much lower proportion of patients than originally estimated. A previously validated liver tissue transcriptional biomarker test was not considered accurate in predicting the success of immunosuppression withdrawal. Study registration Current Controlled Trials ISRCTN47808000 and EudraCT 2014-004557-14. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Efficacy and Mechanism Evaluation (EME) programme (NIHR award ref: 13/94/55) and is published in full in Efficacy and Mechanism Evaluation; Vol. 12, No. 3. See the NIHR Funding and Awards website for further award information. Plain language summary After liver transplantation, the body’s immune system may reject the transplanted organ. In order to prevent rejection, the immune system has to be weakened or suppressed by administering anti-rejection medications. The majority of liver transplant patients need to take the anti-rejection drugs for life, which can be problematic due to their many side effects. However, years after transplantation, a small group of patients can stop their anti-rejection drugs without undergoing rejection. This phenomenon is known as transplantation tolerance. In a study completed in 2012, it was possible to identify liver transplant patients who had developed tolerance with high precision by conducting a genetic test in a liver biopsy. The objective of the current clinical trial was to validate this test of tolerance. This was done by enrolling patients more than 3 years after transplantation and allocating them at random to two groups. All the patients in group A had their anti-rejection medication gradually discontinued, while in group B only those patients who had a positive test result had their anti-rejection medication weaned. The expectation was that more patients would be able to stop their anti-rejection medication in group B than in group A. One hundred and twenty-two patients were enrolled in the trial, out of whom 80 patients attempted to discontinue the anti-rejection drugs, while 34 patients maintained their normal medications. Among patients who attempted to stop anti-rejection drugs, 67.5% developed rejection, 27.5% completely stopped the anti-rejection drugs, but 16% were considered as truly tolerant after having had a liver biopsy. Overall, drug discontinuation was successful in a much lower proportion of patients than originally predicted. Furthermore, the test of tolerance was not accurate enough to identify tolerant patients before initiating anti-rejection drug discontinuation. As a result of the diagnostic test not performing as expected, the trial had to be terminated prematurely. Scientific summary Background Long-term survival following liver transplantation has not significantly improved over the past 30 years, with long-term sequelae from chronic immunosuppression, including infections and cancer, being the most common causes of death. Long-term surviving liver transplant recipients can spontaneously develop operational tolerance, which allows them to completely discontinue their immunosuppression, but we lack validated tools to predict the likelihood of rejection following immunosuppression withdrawal. A previous clinical trial showed that a logistic regression algorithm including the transcript levels of a set of five genes in a liver biopsy could predict the success of immunosuppression withdrawal with high sensitivity and specificity. Objective To determine if the use of a liver tissue transcriptional test of tolerance to stratify liver recipients prior to immunosuppression withdrawal accurately identifies operationally tolerant recipients and reduces the incidence of rejection, as compared with a control group in whom immunosuppression withdrawal is performed without stratification. Methods Design The liver immunosuppression free trial (LIFT) was a prospective, multicentre, phase IV, biomarker-strategy design trial with a randomised control group in which adult liver transplant recipients were randomised 1 : 1 to either: (1) non-biomarker-based immunosuppression (IS) weaning (Arm A); or (2) biomarker-based IS weaning (Arm B). Participants: liver transplant recipients ≥ 3 years post transplant (≥ 6 years if age ≤ 50 years old) with no history of autoimmunity or recent episodes of rejection, normal allograft function, and no significant histological abnormalities in a baseline screening liver biopsy, recruited from 12 transplant units in UK, Germany, Belgium and Spain. Intervention Enrolled patients underwent a screening liver biopsy to exclude the presence of subclinical allograft damage. Eligible participants randomised to Arm A underwent gradual discontinuation of immunosuppression over a 6 to 9-month period. Among participants allocated to Arm B, only those found to be biomarker-positive were offered immunosuppression withdrawal (as in Arm A), while biomarker-negative participants remained on their baseline maintenance immunosuppression. Patients who completely discontinued immunosuppression and maintained stable allograft function underwent protocol liver biopsies at 12 and 24 months after immunosuppression withdrawal to confirm histological criteria of operational tolerance (as previously described by the Banff Liver Histopathology Group). Main outcome measure The primary end point was the development of operational tolerance, defined as the successful discontinuation of immunosuppression with maintenance of normal allograft status, as assessed by liver biopsy and liver tests 12 and 24 months after immunosuppression withdrawal. Results Of the 122 patients eligible to participate in the trial, 116 randomised (58 to Arm A and 58 to Arm B), 80 initiated immunosuppression withdrawal and 34 were maintaining on their baseline immunosuppression. Among the 80 patients who initiated immunosuppression withdrawal, 54 (67.5%) developed clinically apparent rejection, 22 (27.5%) successfully discontinued immunosuppression, 21 underwent a liver biopsy and 13 (16.3%) met the histological criteria of operational tolerance at 12 months after immunosuppression discontinuation. The remaining four patients were withdrawn from the study before developing rejection or reaching the primary end point. Ten out of the 56 (18%) of patients who initiated immunosuppression withdrawal in Arm A achieved operational tolerance at 12 months versus 3 among the 24 patients (13%) who initiated withdrawal in Arm B. The performance evaluation of the transcriptional tolerance biomarker showed that the test was not accurate at identifying patients meeting the operational tolerance criteria (odds ratio 1.466, 95% IC 0.326 to 9.215; p = 0.744; Sn 54%, Sp 42%, positive predictive value 16%, and negative predictive value 81%, with an accuracy of 44%). Due to the poor diagnostic performance of the test, the trial was terminated prematurely following an interim analysis of the results. Following the protocol liver biopsy performed 24 months after withdrawal, 16 out of the 21 who underwent a liver biopsy 12 months after IS discontinuation were considered not to require immunosuppression, 15 (18.8% of the 80 patients who initiated IS withdrawal) of whom met operational tolerance histology criteria. No patients lost their grafts as a result of rejection during the study duration. Subclinical histological abnormalities indicative of active alloimmune damage in patients considered non-eligible to participate in the trial were associated with serum transaminases, donor-specific antibodies and/or transient elastography measurements. Conclusions Immunosuppression withdrawal proved to be feasible and safe but was successful in a much lower proportion of subjects than originally estimated. A liver tissue biomarker test previously validated in a population of liver transplant recipients with a much higher prevalence of operational tolerance, was not accurate in predicting the success of immunosuppression withdrawal. As a result, the trial had to be terminated prematurely and did not meet its objectives. The use of non-invasive markers such as serum transaminases, donor-specific antibodies and transient elastography is useful to identify stable liver transplant recipients with active underlying graft alloimmunity despite receiving immunosuppression. Study registration Current Controlled Trials ISRCTN47808000 and EudraCT 2014-004557-14. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Efficacy and Mechanism Evaluation (EME) programme (NIHR award ref: 13/94/55) and is published in full in Efficacy and Mechanism Evaluation; Vol. 12, No. 3. See the NIHR Funding and Awards website for further award information.